Здійснення психологом процесу посередництва при подоланні конфліктів - Черкасова, Анна Вадимівна; Cherkasova, Anna Vadymivna (Ірпінь, 2023)
У першому розділі проводиться теоретико-методологічний аналіз проблем посередництва як альтернативного способу розв’язання психологом конфліктів. У другому розділі описані технологічні особливості здійснення процесу посередництва психологом. У третьому розділі наводяться результати вивчення психологічних особливостей поведінки спеціалістів чергової пожежної частини ДСНС та динаміка особистісних змін у членів тренінгової групи. Одержані результати можуть бути використані як практичне керівництво для регуляції психологом - посередником міжособистісного конфлікту спеціалістів колективу чергової пожежної частини ДСНС.

In the first chapter, a theoretical and methodological analysis of mediation problems is carried out as an alternative way for psychologists to resolve conflicts. The second chapter describes the technological features of the mediation process by a psychologist. In the third section, the results of the study of the psychological characteristics of the behavior of specialists of the emergency fire department of the State Emergency Service and the dynamics of personal changes in the members of the training group are presented. The obtained results can be used as a practical guide for the regulation by a psychologist - a mediator of interpersonal conflict of specialists of the staff of the emergency fire department of the State Emergency Service.
Implementation by a psychologist of the process of mediation in overcoming conflicts
Keywords: конфлікти; конфліктність; посередництво; психолог - посередник; рятувальники; підрозділ ДСНС; чергова пожежна частина ДСНС; тренінг; conflicts; conflict; mediation; psychologist - mediator; rescuers; a division of the State Emergency Service; on-call fire department of the State Emergency Service; training